Examining the Key Drivers of Customer Loyalty in the Coffee Retail Industry: Evidence from Starbucks Customers - Yee Huei Lok; Lay Hong Tan; Ranjith PV; Kishan Singh Rathore; Pui Zhi Cheong; Kah Song Chew; Wei Yi Chew; Jia Sheng Chia; Anas Anas; Pratishthit Chauhan; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
Starbucks is one of the leading global coffeehouse chains known for its strong brand presence and customer-centric approach. However, in today’s highly competitive food and beverage market, maintaining customer loyalty and encouraging repeat purchases remain crucial challenges. This study aims to examine the key factors influencing customer loyalty toward Starbucks, focusing on service quality, perceived value, product quality, and price. A quantitative research design was adopted using a structured questionnaire distributed through Google Forms to customers who have purchased from Starbucks. The data will be analyzed using statistical techniques to examine the correlations among the variables. Our findings show that perceived value, product quality, and price have significant positive effects on customer loyalty. However, service quality has non-significant negative effects on customer loyalty. The results of this study will provide valuable managerial insights to enhance marketing strategies, strengthen customer engagement, and maintain long-term loyalty. This study also contributes to the understanding of customer behavior in the food and beverage industry, particularly within international coffeehouse brands